2020
DOI: 10.1108/imefm-09-2019-0382
|View full text |Cite
|
Sign up to set email alerts
|

How and when Islamic work ethic (IWE) leads to employee promotive and prohibitive voice? The interplay of employee moral identity and perceived voice opportunity

Abstract: Purpose This study aims to examine the moderated-mediation effects of employees’ Islamic work ethic (IWE) on their promotive and prohibitive forms of constructive voice behaviors through the integrated frameworks of social identity theory and self-consistency theory. Design/methodology/approach Using two-source data collection from em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 74 publications
(187 reference statements)
0
3
0
Order By: Relevance
“…Moreover, studies have identified Islamic work ethics as significant in the modern era because ethics have become a central element due to their benefits for all generations (Nasution and Rafiki, 2020). Islamic work ethic is a set of Islamic work-related concepts and values that assist believers to distinguish between bad and good work attitudes and actions (Hameed et al , 2020). Islamic work ethic is linked to a variety of situational factors, attitudes and actions of employees including organizational commitment (Nasution and Rafiki, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, studies have identified Islamic work ethics as significant in the modern era because ethics have become a central element due to their benefits for all generations (Nasution and Rafiki, 2020). Islamic work ethic is a set of Islamic work-related concepts and values that assist believers to distinguish between bad and good work attitudes and actions (Hameed et al , 2020). Islamic work ethic is linked to a variety of situational factors, attitudes and actions of employees including organizational commitment (Nasution and Rafiki, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Second, this study extends the relationship between IWE and employee voice from previous studies (Akhmadi et al, 2023;Hameed et al, 2020). Prior research in the Asian context generally studied IWE as determinant of social behavior (Murtaza et al, 2016;Suryani et al, 2022), knowledge sharing (Suryani et al, 2021), and innovation (Kumar & Che Rose, 2010.…”
Section: Introductionmentioning
confidence: 53%
“…Furthermore, IWE create such a culture that encourages employees to go the extra mile in the workplace by helping co-workers and creating a good corporate image. In today's competitive world employees' tacit knowledge and employees strong bound with organization and co-workers are only additional factor to become great organization, that why the study aspire to explain the role of IWE to engage employees in knowledge sharing and organizational citizenship behaviors rather than western workplace environment (Hameed, Bhatti, Khan, & Syed, 2020).…”
Section: Introductionmentioning
confidence: 99%